Influence of Retrogression and Reaging Treatment on Microstructure and Microhardness of the 3A21/7075 Aluminum Alloy Cladding Material - Ming Hu; Xiaoxue Ren; Jianbo Sun; Yunlong Zhang (International Journal of Photoenergy)
The 7075 aluminum alloy was an important structural material in the field of aeronautics and astronautics. With the development of this field, the requirements for its comprehensive properties were increasing. A novel casting method, the impact jet solid-liquid compound casting, was adopted to fabricate the 3A21/7075 aluminum alloy cladding material. Retrogression and reaging (RRA) treatment was further applied to the 3A21/7075 aluminum alloy cladding material in order to investigate the influence of RRA on microstructure and microhardness of the 3A21/7075 aluminum alloy cladding material. Then, the electron backscattered diffraction (EBSD) technique and the transmission electron microscope (TEM) together with the energy dispersive spectrometer (EDS) and the hardness test were utilized to analyze the influence of RRA treatment on microstructure and hardness of the 3A21/7075 aluminum alloy cladding material. The research results showed the 3A21/7075 aluminum alloy cladding material had better deformability. The amount of fine and dispersed phases precipitated in grains was in favor of improving the comprehensive mechanical properties of the 3A21/7075 aluminum alloy cladding material. This research might provide data and a theoretical approach for the engineering application of the 3A21/7075 aluminum alloy cladding material.